2016
DOI: 10.1007/s00106-016-0285-9
|View full text |Cite
|
Sign up to set email alerts
|

Intracochlear drug delivery in combination with cochlear implants

Abstract: Local drug application to the inner ear offers a number of advantages over systemic delivery. Local drug therapy currently encompasses extracochlear administration (i. e., through intratympanic injection), intracochlear administration (particularly for gene and stem cell therapy), as well as various combinations with auditory neurosensory prostheses, either evaluated in preclinical or clinical studies, or off-label. To improve rehabilitation with cochlear implants (CI), one focus is the development of drug-rel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
67
0
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 86 publications
(68 citation statements)
references
References 62 publications
(72 reference statements)
0
67
0
1
Order By: Relevance
“…Both substances were administrated intravenously 60 min before implantation. As a final conclusion, authors stressed that dexamethasone could reduce scarring process as the electrode negotiated the hook region or near the electrode tip, but they did not observe the relation between dexamethasone and reduction of fibrosis relating to cochleostomy [13]. In vitro studies showed the correlation between reduction (loss) of auditory cells after exposure to tumor necrosis factor alpha (TNF-alpha) and dexamethasone-releasing polymer used to coat electrode of cochlear implant carries.…”
Section: Pharmacokinetics Of Glucocorticoids and Studies On Animal Modelmentioning
confidence: 98%
See 2 more Smart Citations
“…Both substances were administrated intravenously 60 min before implantation. As a final conclusion, authors stressed that dexamethasone could reduce scarring process as the electrode negotiated the hook region or near the electrode tip, but they did not observe the relation between dexamethasone and reduction of fibrosis relating to cochleostomy [13]. In vitro studies showed the correlation between reduction (loss) of auditory cells after exposure to tumor necrosis factor alpha (TNF-alpha) and dexamethasone-releasing polymer used to coat electrode of cochlear implant carries.…”
Section: Pharmacokinetics Of Glucocorticoids and Studies On Animal Modelmentioning
confidence: 98%
“…Two main groups of drugs are used in clinical practice: aminoglycoside (mainly gentamicin) in pharmacotherapy of Meniere's disease [10] and corticosteroids (dexamethasone, triamcinolone and dexamethasone) in pharmacotherapy of idiopathic sudden sensorineural hearing loss (ISSHL) and other cases of acute hearing loss [11]. The inner ear from a pharmacokinetic point of view is a multicompartment model [12,13] with stable fluids and balance between them (due to the presence of blood-labyrinth barrier (BLB)). Distribution process depends on many different factors such as route of administration, model of administration (single or repeated administration), dose of medicine, ionic composition, and pH or osmolarity of solution.…”
Section: Pharmacokinetics Of Glucocorticoids and Studies On Animal Modelmentioning
confidence: 99%
See 1 more Smart Citation
“…Important aspects of novel hearing restoration strategies including gene therapy [3], stem cells [4,5], and related intracochlear distribution nanotechnologies [6,7] are still at best in a preclinical phase.…”
Section: Introductionmentioning
confidence: 99%
“…Nevertheless, many open questions exist in relation to drug delivery the ear. They include (adapted from Salt and Plontke, 2009 and Plontke et al 2017): 1) choice of drug, 2) choice of delivery strategy (systemic, local intratympanic, local intracochlear / intralabyrinthine, combined local and systemic, or directly via an auditory implant); 3) timing of application, including the consideration of chronopharmacological issues especially for drugs with short half-lives (Canlon 2018); 4) choice of formulation and/or drug carrier; 5) choice of drug delivery system; 6) dose to apply; 7) risk–benefit ratio of the therapy; and 8) obstacles to successfully test a promising candidate therapy in a clinical trial.…”
mentioning
confidence: 99%